Efektivitas Efektivitas Model Discovery Learning Terhadap Kemampuan Menulis Resensi Berdasarkan Cerpen Yang Ditulis Oleh Teman Siswa : Efektivitas Model Discovery Learning Terhadap Kemampuan Menulis Resensi Berdasarkan Cerpen Yang Ditulis Oleh Teman Siswa - Marjulita Lita; Upit Yulianti DN; Trisna Helda (Signifiѐ, 2024)
This research is motivated by the ability to write reviews based on short stories written by fellow students using the Discovery Learning model with a quantitative research type, the research design used is one group pretest, post test, design. The population in this study were students of the F after using the Discovery Learning model it became 81.16 with Quality in the range of 76-85% good qualifications (B).